Pengaruh Kecerdasan Emosional, Intelektual, Spiritual, dan Sosial terhadap Kualitas Kehidupan Kerja Pegawai: Studi pada Kecamatan Seram Barat, Kabupaten Seram Bagian Barat - Ricky CH Mandaku; Mohamad Arsad Rahawarin; Aminah Bahasoan (MAN 4 Kota Pekanbaru, 2025)
This study investigates how multiple facets of intelligence shape the quality of work life among employees serving in the West Seram District Office, West Seram Regency. Employing a descriptive–quantitative design with a causal-correlational framework, the research positions the intelligence dimensions as determinants of variations in employees’ work-life quality. The entire workforce—comprising 19 civil servants, 4 government contract staff (P3K), and 26 honorary employees—was included as the sample through a full-enumeration technique, totaling 49 respondents. Data processing was carried out using multiple linear regression to identify the contribution of each intelligence dimension. The findings reveal that emotional, intellectual, spiritual, and social intelligence each exert a significant and positive influence on the quality of work life. These results underscore the importance of developing holistic intelligence capacities to enhance workplace well-being within public sector institutions.